Easy Women : Sex And Gender In Modern Mexican Fiction - Castillo, Debra A. (Book collections on Project MUSE., 1998)
Combining early twentieth-century novels, current best-selling pulp fiction, and testimonial narratives, Castillo explores how Mexican writers have positioned the "easy woman" in their works.